2022
DOI: 10.1109/access.2022.3170430
|View full text |Cite
|
Sign up to set email alerts
|

Physics-Based Digital Twins Merging With Machines: Cases of Mobile Log Crane and Rotating Machine

Abstract: Real-world products and physics-based simulations are becoming interconnected. In particular, real-time capable dynamic simulation has made it possible for simulation models to run in parallel and simultaneously with operating machinery. This capability combined with state observer techniques such as Kalman filtering have enabled the synchronization between simulation and the real world. State estimator techniques can be applied to estimate unmeasured quantities, also referred as virtual sensing, or to enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 70 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…The robustness of the algorithm is validated through a simulation model based on Lorenz process and an industrial diesel hydrotreating case. A research work in [ 23 ] presented technical features of merging machinery with a physics-based DTs based on EKF methods for providing successful implementation information. In this regard, two industrial processes were analyzed to demonstrate the methodology; the first is a mobile log crane, which is applicable for the heavy mobile machinery, and the second process concerned a rotating electric machine in case of unexpected failures.…”
Section: Introductionmentioning
confidence: 99%
“…The robustness of the algorithm is validated through a simulation model based on Lorenz process and an industrial diesel hydrotreating case. A research work in [ 23 ] presented technical features of merging machinery with a physics-based DTs based on EKF methods for providing successful implementation information. In this regard, two industrial processes were analyzed to demonstrate the methodology; the first is a mobile log crane, which is applicable for the heavy mobile machinery, and the second process concerned a rotating electric machine in case of unexpected failures.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, realtime capable simulation models enable the development of digital twins that can operate in parallel to the actual machine, and therefore give insights into the machine and its operation. For example, multibody-based methods are highly capable in dynamic applications, e.g., in mobile heavy machinery, providing high accuracy, computational efficiency, and real-time capability [1]- [3]. Real-time capability is desired, because it can be used, for example, in simulators that respond to real-time commands, i.e., operating the virtual machine in the same way as its physical counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the multibody formulations can be combined with VOLUME 4, 2016 state and parameter estimation methods, [8]- [11] to enhance the measurement data of a real system, [12]- [14]. The estimated data provides information about the unknown states and parameters, which can be used in the wide range of condition monitoring and predictive maintenance of the real system [3], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Rotating machinery is an indispensable main equipment in industrial machinery because of its unique properties and functions [ 2 ]. Typical rotating machinery includes gearboxes, reducers, steam turbines, gas turbines, fans, generators, and engines, which are widely used in electric power, petrochemical, metallurgy, automobile manufacturing, aerospace, and other sectors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the research, it is found that the bearing damage fault accounts for about 40% of the faults of rotating machinery, and the fault caused by gear failure accounts for about 10.3%. Therefore, it is of great significance to find out the fault conditions in the rotating machinery in time and conduct accurate fault diagnosis and maintenance for the rotating machinery to ensure the safe and stable operation of the production system and reduce the probability of catastrophic accidents [ 3 ].…”
Section: Introductionmentioning
confidence: 99%